The Role of Muslim Families in Children's Education on Environmental Ethics - Alfiyanto, Afif; Ikhwan, M.; Syafrullah, Haidir; Mahdi, Mahdi; Hidayati, Fitri (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2024)
This study examines the role of Muslim families in children's education regarding environmental ethics. It aims to understand how Muslim parents' integration of Islamic values such as amanah, caliphate, and tawhid can effectively instill awareness and pro-environmental behavior in children. This research explores various parenting methods, including stories from the Qur'an and Hadith, practical activities like gardening and recycling, and discussions and reflections on environmental issues using the literature review method. The findings reveal that children educated with this approach exhibit high ecological awareness and proactive behavior in ecological conservation. However, challenges such as lack of knowledge and resources and differences in cultural and geographical contexts affect the effectiveness of this education. The study concludes that there is a need for support from formal education institutions and communities to strengthen environmental education at home. With the right approach and adequate support, environmental education based on Islamic values has excellent potential to form a generation that cares about the environment. This research provides important insights for developing holistic environmental education programs rooted in religious values.